Morphological and molecular study of Microphallus primas (Digenea: Microphallidae) metacercaria, infecting the shore crab Carcinus maenas from northern Portugal - Pina, Susana; Russell-Pinto, Fernanda; Rodrigues, Pedro (Folia parasitologica, 2011)
The present study describes the anatomy and surface topography of the metacercaria of Microphallusprimas (Jägerskiöld, 1909) infecting the shore crab Carcinus maenas (L.) in Aveiro estuary, northern Portugal. The metacercaria species identification resulted from the combined use of morphological and molecular data, particularly the 28S rDNA gene. The metacercariae encysted preferentially in the host's hepatopancreas and also in the gonads. Isolated cysts were present in two distinct forms, spherical and oval, and were shown to be the identical species by the internal transcribed spacer 1 (ITS1) sequence. Chemically excysted metacercariae were studied by light (LM) and scanning electron microscopy (SEM). Their specific characteristics observed include the particular aspect of the vesiculo-prostatic pouch surrounded by a very thin membrane, the presence of a prominent muscular papilla, and an obvious metraterm. The dorsal and ventral tegumental surfaces of the metacercaria were densely packed with similar squamous spines, which decreased in number and size towards the hindbody. The edges of the posterior and ventral face of the body were coated with numerous microvilli, whose function remains unknown. In order to identify the species of metacercariae, we compared a 28S partial rDNA sequence of the two forms of cysts with the same 28S partial region of M. primas available in GenBank. With this comparison, we determined that the sequences had a 100% similarity and therefore belonged to the same species, i.e., M. primas.
Keywords: DNA helmintů; DNA, Helminth; sekvence nukleotidů; Male; metacerkárie; Sequence Analysis, DNA; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; Metacercariae; mužské pohlaví; mezerníky ribozomální DNA; krabi; larva; Animals; ženské pohlaví; Microscopy, Electron, Scanning; Brachyura; zvířata; Trematoda; Financing, Organized; Portugal; DNA, Ribosomal Spacer; Molecular Sequence Data; Base Sequence; Larva; DNA, Ribosomal; Female; financování organizované; mikroskopie elektronová rastrovací; Portugalsko